Simple and Efficient Synthesis of Allyl Sulfones through Cs2CO3-Mediated Radical Sulfonylation of Morita–Baylis–Hillman Adducts with Thiosulfonates - Shankar, Angothu; Waheed, Md.; Reddy, Raju Jannapu (SynOpen, 2021)
A highly efficient and eco-friendly method has been developed for the synthesis of allyl sulfones using Morita–Baylis–Hillman (MBH) adducts and thiosulfonates under mild conditions. The Cs2CO3-promoted radical sulfonylation provided a series of allyl sulfones in good to high yields with high stereoselectivities. A wide variety of MBH bromides/acetates as well as thiosulfonates were tolerated and reliable in scaled-up synthesis. A plausible mechanism is proposed to rationalize the radical sulfonylation.
Keywords: allyl sulfones; cesium carbonate; MBH adducts; radical sulfonylation; thiosulfonates